Translanguaging in Higher Education: Students’ Perceptions and Its Pedagogical Implications - Liu, Ya Jun (Trinity College (Dublin, Ireland). School of Education, 2022)
This dissertation attempts to synthesise the literature on translanguaging practised in diverse academic disciplines and social contexts, especially in the context of higher education. Its primary purpose is to use an online questionnaire to investigate postgraduate students’ perceptions of translanguaging in Irish higher education and shed light on the pedagogical implications for bilingual and multilingual learners in the 21st century. This study aimed to contribute to the existing knowledge of bilingual and multilingual students’ attitudes towards translanguaging: firstly, as language practice; secondly, for second language learning; thirdly, in social settings; fourthly, in higher education contexts. This study revealed the postgraduate students’ highly positive perceptions of translanguaging practice among all four aspects. They were highly positive about engaging in translanguaging practice and agreed that translanguaging is socially acceptable. These results shed some light on the implications of four different pedagogical perspectives: translanguaging theories and practices development for teachers; safe spaces for students’ translanguaging practices; teacher-student role in the classroom; pedagogical contexts. A key conclusion of this study was that translanguaging was perceived as a resource, a natural social practice, and acceptable language employment in higher education contexts, which can facilitate students’ understanding within the classroom and extend their knowledge beyond the classroom. It is suggested that further study could be conducted on classroom observations to determine instructors' language policies, practices, and their implementation of translanguaging pedagogy. Moreover, it should focus on other complex contexts and multilingual educational variations to explore teachable pedagogic resources for bilingual and multilingual learners.
Keywords: Language Education; Education